Hypothalamic arcuate nucleus glucokinase regulates insulin secretion and glucose homeostasis. Issue 9 (12th June 2018) - Ma, Yue; Ratnasabapathy, Risheka; Izzi‐Engbeaya, Chioma; Nguyen‐Tu, Marie‐Sophie; Richardson, Errol; Hussain, Sufyan; De Backer, Ivan; Holton, Christopher; Norton, Mariana; Carrat, Gaelle; Schwappach, Blanche; Rutter, Guy A.; et al.
Abstract : Aims: To investigate the role of arcuate glucokinase (GK) in the regulation of glucose homeostasis. Materials and methods: A recombinant adeno‐associated virus expressing either GK or an antisense GK construct was used to alter GK activity specifically in the hypothalamic arcuate nucleus (arc). GK activity in this nucleus was also increased by stereotactic injection of the GK activator, compound A. The effect of altered arc GK activity on glucose homeostasis was subsequently investigated using glucose and insulin tolerance tests. Results: Increased GK activity specifically within the arc increased insulin secretion and improved glucose tolerance in rats during oral glucose tolerance tests. Decreased GK activity in this nucleus reduced insulin secretion and increased glucose levels during the same tests. Insulin sensitivity was not affected in either case. The effect of arc GK was maintained in a model of type 2 diabetes. Conclusions: These results demonstrate a role for arc GK in systemic glucose homeostasis.